TUGAS SERTA PERAN DEWAN PENGAWAS SYARIAH DALAM PENERAPAN PRINSIP SYARIAH DI BMT L-RISMA - Sholeh, M. (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
Non-Bank Sharia financial institutions themselves have the obligation to have a Sharia Supervisory Board as mentioned in article 32 of the general provisions of the Decree of the Minister of Cooperatives and Small and Medium Enterprises Number 91 of 2004 concerning KJKS which states legally and clearly that the existence of DPS has its own position to report the results of its supervision. to the government, in this case the Ministry of Cooperatives. The author's methodology is to use two problem approaches, namely an empirical juridical approach and a normative juridical approach. The role of the sharia supervisory board in supervising sharia aspects at (Baitul Maal Wa Tamwil) BMT L Risma is to carry out periodic supervision of the BMT L Risma financial institution, submit proposals for the development of sharia financial institutions to the relevant BMT L Risma leadership and to the DSN, report BMT L Risma's development of sharia finance products and operations which he supervises with DSN at least twice in one fiscal year, formulates problems that require discussion with DSN, to carry out this supervision, DPS members must have integral scientific qualifications, namely the science of muamalah fiqh and modern Islamic financial economics